The free song (hymn) as a means of expression of the spirituality of the local congregation with specific focus on the situation of the Dutch Reformed Church in South-Africa - Vos, C.J.A. (Casparus Johannes Adam), 1945- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2011.